Health Literacy Development among People with Chronic Diseases: Advancing the State of the Art and Learning from International Practices - Dierks, Marie-Luise; Lander, Jonas; Hawkins, Melanie (2022)
Chronic diseases account for a considerable part of the strain on health care systems and are burdensome for each affected individual and their families. In recent years, the concept of health literacy has been substantially elaborated on, particularly regarding the development and implementation of interventions at different levels, efforts to improve its measurement, and the role of communities and organizations. While a range of advancements are uncontested, specific challenges still revolve around, for example, a thorough application of modern practices of health literacy that focus on societal support of health literacy strengths and response to health literacy challenges; developing, testing, and evaluating strategies for organizational health literacy responsiveness; and improving the co-design, local ownership, and integration of health literacy actions and interventions in communities experiencing vulnerability and disadvantage. This Special Issue showcases research addressing these and further aspects about developing health literacy - particularly among people with chronic diseases - by which we mean advancements in health practices, organizations, and policies that create enabling environments in which people have the necessary knowledge and feel confident accessing, understanding, and using health information and services.